2013
DOI: 10.1002/jez.1795
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Interaction Between Attractant Diacetyl and Repellent 2‐Nonanone in the Nematode Caenorhabditis elegans

Abstract: In the nematode Caenorhabditis elegans, the odorant diacetyl is sensed by AWA sensory neurons in the amphid sensory organ and elicits an attractive response, whereas 2-nonanone is sensed by AWB amphid sensory neurons and elicits an avoidance response. In the present study, we report that nematodes exhibit a sensory interaction between the attractant diacetyl and repellent 2-nonanone. In the presence of food, the chemotactic response to 0.01% diacetyl in nematodes preexposed to 0.1% diacetyl was greater than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…IFT mutations decrease sensory responses in most ciliated sensory neurons (Inglis et al, 2007), but AWA had robust calcium responses across a range of odor concentrations in che-2, che-3 and osm-6 mutants (Figure 4a,b), and only mild defects in diacetyl chemotaxis at the concentrations at which AWA is required (Bargmann et al, 1993; Matsuura et al, 2013; Figure S3). All of the IFT mutants had abnormal AWA cilia, in agreement with previous studies (Figure 4c, S3 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…IFT mutations decrease sensory responses in most ciliated sensory neurons (Inglis et al, 2007), but AWA had robust calcium responses across a range of odor concentrations in che-2, che-3 and osm-6 mutants (Figure 4a,b), and only mild defects in diacetyl chemotaxis at the concentrations at which AWA is required (Bargmann et al, 1993; Matsuura et al, 2013; Figure S3). All of the IFT mutants had abnormal AWA cilia, in agreement with previous studies (Figure 4c, S3 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Staged young adults (obtained by growing the progeny of bleached gravid adults) (Porta‐de‐la‐Riva et al, 2012) were used for chemotaxis assays (Figure 2a, b). Attraction to diacetyl and avoidance to SDS were assessed in quadrant assays, as described (Matsuura et al, 2013). Briefly, a 10‐cm‐diameter tissue culture dish containing 0.001 M CaCl 2 , 0.001 M MgSO 4 , 0.2 M KH 2 PO 4 buffer, 0.5 mg/ml cholesterol and agar was divided into four quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type N2 C. elegans (strain N2) was obtained from the Caenorhabditis Genetics 91 Centre, University of Minnesota, Minneapolis, USA, and was cultured on Nematode Growth Medium. Chemosensory assays were performed as described by [ 29 ] with some minor modifications.…”
Section: Methodsmentioning
confidence: 99%